A transparência passiva na Universidade Federal da Paraíba - Barros, Savia Rodrigues Martins (2017)
The present research aims to investigate how passive transparency, which is the right that the citizen or any entity of civil society has to demand information from the State, can enhance social participation, enabling a more democratic and participatory university . It is appropriate to investigate whether university transparency practices are adequate in accordance with the LAI. It is understood as relevant to answer the following: How does the UFPB come providing public transparency? Is it meeting the demand of the university public? For that, we used the dialogue with the theorists Antunes (2004); Bobbio (2004, 2015); Campos (1990); Chauí (2001); Casttels (2010); Santos (2014), Lévy (2002 and 2010) and other references that address the thematic pertinence and context of public policies in higher education. The methodology used was anchored in the qualitative, dialectical approach. It was also used the research of the monographic and field type using the tripod: bibliographical, documentary and data collection, through the application of a questionnaire, finally, we proceeded the content analysis, thematic analysis type. The final results pointed out that UFPB's university public still does not use all available institutional transparency resources and that such channels still need to be improved to meet current demands and enable better communicability and democratization of access to information.